A critical role for IRF5 in regulating allergic airway inflammation - Byrne, A; Weiss, M; Mathie, S; Walker, S; Eames, H; Saliba, D; Lloyd, C; Udalova, I (Nature Publishing Group, 2016)
Interferon regulatory factor 5 (IRF5) is a key transcription factor involved in the control of the expression of pro-inflammatory cytokine and responses to infection, however its role in regulating pulmonary immune responses to allergen is unknown. We used genetic ablation, adenoviral vector-driven overexpression and adoptive transfer approaches to interrogate the role of IRF5 in pulmonary immunity and during challenge with the aero-allergen, house dust mite. Global IRF5 deficiency resulted in impaired lung function and extracellular matrix (ECM) deposition. IRF5 was also essential for effective responses to inhaled allergen, controlling airway hyper-responsiveness, mucus secretion and eosinophilic inflammation. Adoptive transfer of IRF5-deficient alveolar macrophages into the WT pulmonary milieu was sufficient to drive airway hyper-reactivity, at baseline or following antigen challenge. These data identify IRF5-expressing macrophages as a key component of the immune defence of the airways. Manipulation of IRF5 activity in the lung could therefore be a viable strategy for the redirection of pulmonary immune responses and thus, the treatment of lung disorders.